2019
DOI: 10.1186/s12890-019-0834-6
|View full text |Cite
|
Sign up to set email alerts
|

Supporting medication adherence for adults with cystic fibrosis: a randomised feasibility study

Abstract: Background Preventative medication reduces hospitalisations in people with cystic fibrosis (PWCF) but adherence is poor. We assessed the feasibility of a randomised controlled trial of a complex intervention, which combines display of real time adherence data and behaviour change techniques. Methods Design: Pilot, open-label, parallel-group RCT with concurrent semi-structured interviews. Participants: PWCF at two Cystic Fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 88 publications
0
37
0
Order By: Relevance
“…The adherence data used in this study was recorded using the same method as previous work in the area [12]. Objective adherence to the eTrack®system (Pari GmbH, Stanberg, Germany) was recorded along with the patients' prescription.…”
Section: Adherence Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The adherence data used in this study was recorded using the same method as previous work in the area [12]. Objective adherence to the eTrack®system (Pari GmbH, Stanberg, Germany) was recorded along with the patients' prescription.…”
Section: Adherence Datamentioning
confidence: 99%
“…Adherence to nebuliser treatments is poor [12] and there is a large difference between self-reported and objective adherence rates. Daniels et al [13] found that adults self-reported 80% adherence levels, which corresponded with an adherence rate of only 36% for this group when using objective nebuliser reports taken from the I-neb adaptive aerosol delivery (AAD) nebuliser system (Philips Respironics; Chichester, England).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximizing adherence requires an honest and open relationship with the individual and flexibility from health care practitioners to understand what an individual can do and to help them prioritize their treatment program. 126 Chipped inhalers and nebulizers may provide valuable biofeedback and actual data to improve patient/health care team discussions. 127 The MDT pharmacist, physiotherapist, and psychologist can all make helpful contributions to facilitating the most efficient use of medicines in individual patients.…”
Section: Treatment Burden and Adherencementioning
confidence: 99%
“…28 29 In response, a complex intervention was developed to support inhaled medication adherence in PWCF. 30 This article presents the results of a process evaluation that was undertaken alongside a pilot randomised controlled trial (RCT), the objectives of which were to determine the feasibility of a full-scale RCT. 30 Here, we describe the resultant changes made to intervention procedures prior to that full-scale RCT.…”
Section: Introductionmentioning
confidence: 99%